Analisis Pelayanan Kementerian Haji dan Umrah terhadap Jama’ah Kota Padangsidimpuan - anisah; Syaiful Bahri Nasuiton; Dedi Al- Fais; Yulia Sari; Samil Khoiri; Armansyah Lubis (Prodi Manajemen Dakwah STAIN Mandailing Natal, 2026)
This study aims to analyze the services of the Ministry of Hajj and Umrah for pilgrims in Padangsidimpuan City, including service quality, existing obstacles, and strategies for service improvement. The research method employed in this study is library research, utilizing various sources such as observation, intervews with operational staff, and previous studies relevant to the research topic. Data analysis was conducted using a qualitative descriptive approach to gain a comprehensive understanding of Hajj and Umrah services in Indonesia, particularly in the context of pilgrims from Padangsidimpuan City. The findings reveal that Hajj and Umrah services have experienced significant improvements, especially in administrative systems, pilgrimage guidance, service digitalization, and information dissemination to pilgrims. However, several challenges remain, including limited human resources, inadequate information dissemination, and administrative obstacles faced by some pilgrims. Therefore, service quality improvement through technology-based systems, enhancement of officers’ competencies, and optimization of public education are necessary to ensure more effective services and greater pilgrim satisfaction.